Application of grain baits to control common vole Microtus arvalis (Pallas, 1778) in alfalfa crops, Serbia - Jokić, Goran; Vukša, Marina; Elezović, Ibrahim; Đedović, Suzana; Kataranovski, Dragan (Archives of Biological Sciences, 2012)
In order to compare the efficacies of conventional (cholecalciferol and bromadiolone) and new (sodium selenite) rodenticides, applied in the grain bait formulation on the whole-grain of wheat (Triticum aestivum) and triticale (Triticasecale) in alfalfa crops, experiments were conducted at two sites near Belgrade, Serbia, in the spring of 2009, using a standard EPPO method. The presence of rodent populations, their spatial distribution and density indices were evaluated by pretreatment census and rodenticide efficacy by counting active holes, 14 and 28 days after treatment. The average Microtus arvalis numbers of 158/ha and 184/ha were found to cause 7.4% and 9.6% alfalfa green biomass yield decreases, respectively. Twenty-eight days after treatment, the average efficacy of grain bait formulation (on wheat and triticale grains) of sodium selenite and cholecalciferol was 81%, while bromadiolone which had a higher efficiency, 85%, in the control of the common vole in alfalfa crops. The analysis of variance (ANOVA) showed that the origin of active substances, bases and associated interactions a.s x based on the efficacy-investigated grain baits did not have a statistically significant impact on the expression efficiency of the tested baits. Triticale grains can be used as carriers of active substances, sodium selenite, cholecalciferol or bromadiolone in preparation baits. Control of M. arvalis with the new rodenticide, sodium selenite, gave efficacy results about equal to that of cholecalciferol and bromadiolone and, therefore, provided a possible alternative rodenticide for vole control in alfalfa.